Rol de los padres para la atención de las discapacidades de sus hijos - Rivas Estupiñán, Mercedes Aracely (2021)
The role of parents is focused on the upbringing and integral development of the child towards autonomy, however, when you have a child with a disability, other tasks of the parents are added that are associated with the type and classification of their disability. The objective of this research was: to analyze the role of parents in caring for children with disabilities. The results obtained reveal that the role is affected, firstly, by the situation of mourning, which occurs when receiving the news, additionally, the inexperience of the parents, since most are young, or it is their first child in the paternal experience. The function of the role of parents and the process of acceptance have an impact on the care of children with disabilities. In this sense, the school becomes a space that favors the care of children's disabilities and the training of parents for their care. One result that should be highlighted in this research is that the child with a disability is generally cared for by the mother, a task in which the father is absent or not involved. From this information obtained, a series of workshops was designed to improve the role of parents of children with disabilities............